Identification of Active Compounds of Tantrum Leaves (Indigofera tinctoria) as Natural Textile Dyes (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
The use of natural dyes as textile dyes is increasing due to environmentally friendly standards and does not require the use of synthetic dyes. By banning the use of synthetic dyes containing azo groups, this is the right moment to reintroduce natural dyes that have been abandoned for a long time. This study aims to identify the active compound of tantrum leaves (Indigofera tinctoria) as a natural textile dye by maceration extraction method with variations in maceration time and material treatment on wet and dry tantrum leaves. This experimental research method was carried out using several stages of analysis, namely the phytochemical test, FTIR (Fourier Transform Infrared Spectroscopy), and UV-Vis (Ultraviolet-Visible Light) spectrophotometer. The results of the phytochemical tests showed that the compounds contained in the Indigofera tinctoria plant were indigo, flavonoids, steroids, and alkaloids. The FTIR test indicated that the dye content in the extract was from the indigo group. The results of the UV-Vis spectrum showed that there was maximum absorption in wet tantrum leaf extract, dry tantrum leaf extract, and alkaline extract at wavelengths of 406.50 nm, 365.50 nm, and 664.50 nm, respectively. Natural dyes in textiles have a positive impact on the environment, the color waste products are biodegradable and can be decomposed.